ANALISIS PENINGKATAN MUTU LEMBAGA PENDIDIKAN PESANTREN MELALUI MANAJEMEN HUMAS - Mahfida Inayati; Mulyadi Mulyadi; Ali Nurhadi (STAI Ma'had Aly Al-Hikam Malang, 2023)
Improving the quality of pesantren educational institutions through public relations management can be done by developing and applying appropriate public relations techniques. Pesantren educational institutions are traditional educational institutions that have their own management but do not deny changes in the current digital era. Public relations has a very important role in the relationship between two parties both from internal and external segments which aims to improve the quality of pesantren educational institutions. So to create a good communication, a good relationship is also needed by making an institution have solid management in the field of public relations. the application of public relations techniques according to Jefrerson and DeRoche theories where the techniques developed are written, oral, demonstration and electronic techniques. Public relations techniques can combine electronic techniques with written, oral or other techniques. This can make it easier for the wider community to get information, ideas or activity reports that can integrate between the institution and the wider community.